Specialized pro-resolving mediators in diabetes: novel therapeutic strategies. (6th November 2019) - Brennan, Eoin P.; Mohan, Muthukumar; Andrews, Darrell; Bose, Madhura; Kantharidis, Phillip
Abstract: Diabetes mellitus (DM) is an important metabolic disorder characterized by persistent hyperglycemia resulting from inadequate production and secretion of insulin, impaired insulin action, or a combination of both. Genetic disorders and insulin receptor disorders, environmental factors, lifestyle choices and toxins are key factors that contribute to DM. While it is often referred to as a metabolic disorder, modern lifestyle choices and nutrient excess induce a state of systemic chronic inflammation that results in the increased production and secretion of inflammatory cytokines that contribute to DM. It is chronic hyperglycemia and the low-grade chronic-inflammation that underlies the development of microvascular and macrovascular complications leading to damage in a number of tissues and organs, including eyes, vasculature, heart, nerves, and kidneys. Improvements in the management of risk factors have been beneficial, including focus on intensified glycemic control, but most current approaches only slow disease progression. Even with recent studies employing SGLT2 inhibitors demonstrating protection against cardiovascular and kidney diseases, kidney function continues to decline in people with established diabetic kidney disease (DKD). Despite the many advances and a greatly improved understanding of the pathobiology of diabetes and its complications, there remains a major unmet need for more effective therapeutics to prevent and reverse the chronic complications of diabetes. More recently, there has been growing interest in the use of specialised pro-resolving mediators (SPMs) as an exciting therapeutic strategy to target diabetes and the chronic complications of diabetes.